2020
DOI: 10.1007/s00500-020-05147-5
|View full text |Cite
|
Sign up to set email alerts
|

Who and where: context-aware advertisement recommendation on Twitter

Abstract: Advertising is becoming a business on social networks. Billions of people around the world use social media, and fastly, it has become one of the defining technologies of our time. Social platforms like Twitter are one of the primary means of communication and information dissemination and can capture the interest of potential customers. Therefore, it is crucial to select suitable advertisements to users in specific times and locations for capturing their attention, profitably. In this paper, we propose a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…An investigation conducted by Lo and Campos [17] examined how companies are integrating IoT solutions into the relationship marketing approaches to determine whether this combination can enhance business performance and what are the challenges with the changes in disruptive technologies. e context-aware advertising recommendation system developed by De Maio et al [18] uses the analysis theory of the triadic formal concept to deduce users' interests and deliver appealing adverts based on their tweets. It was found that a system developed by Deng et al [19] could automatically adapt advertising material to match specific customers' preferences.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…An investigation conducted by Lo and Campos [17] examined how companies are integrating IoT solutions into the relationship marketing approaches to determine whether this combination can enhance business performance and what are the challenges with the changes in disruptive technologies. e context-aware advertising recommendation system developed by De Maio et al [18] uses the analysis theory of the triadic formal concept to deduce users' interests and deliver appealing adverts based on their tweets. It was found that a system developed by Deng et al [19] could automatically adapt advertising material to match specific customers' preferences.…”
Section: Literature Surveymentioning
confidence: 99%
“…e performance of IoT-CFIAR was compared to existing methods such as CAAR, IoT-EDF, and SGS-PAC. Contextual user interest elicitation and the categorization and construction of contextual-aware recommendation algorithms are some of the CAAR drawbacks (De Maio et al, 2021). is drawback has been overcome in this paper using efficient prediction of user interest through MAKNN.…”
Section: Click-rough Ratementioning
confidence: 99%
“…The authors used Yelp 2017 and Amazon review datasets and evaluated their model using mean square error (MSE). In [92], Maio et al developed a context-aware recommendation system using the users' tweets and interactions along the timeline. They included contexts such as (location, time) to identify targeted and personalized advertisements.…”
Section: B Context-aware Recommendation Systems In E-commercementioning
confidence: 99%
“…Twitter offers an application programming interface (API) allows us to collect tweets based on a sample stream, keywords or geo-location, subjected to various collection limits [13], [30]. Due to its public availability, Twitter data has been used for many research works in recent years [31]- [33]. In this work, we used the keywords stream to collect tweets containing the names of various social networks, which are LinkedIn, Instagram, Flickr, Reddit, Tumblr and Pinterest.…”
Section: A Social Media Data Collectionmentioning
confidence: 99%